Snow ice particle microphysical properties and fall speed from particle images taken in Kiruna (Sweden) 2014–2018 (Luleå tekniska universitet, 2021)
Instrumentet Dual Ice Crystal Imager (D-ICI) mäter samtidigt mikrofysikaliska egenskaper och fallhastighet av snöpartiklar. D-ICI tar bilder av partiklar från två olika riktningar med en upplösning av 4μm/pixel. Mätningar med D-ICI i Kiruna, norra Sverige (67.8N, 20.4E), under vintrarna 2014/2015 till 2017/2018 presenteras. Både bilder och egenskaper framtagna av dessa ingår i datasetet. Datasetet ligger till grund för artiklarna Vázquez-Martín, S., Kuhn, T., & Eliasson, S. (2021): Shape dependence of snow crystal fall speed, Atmospheric Chemistry and Physics, 21(10), 7545–7565. https://doi.org/10.5194/acp-21-7545-2021 Vázquez-Martín, S., Kuhn, T., & Eliasson, S. (2021). Mass of different snow crystal shapes derived from fall speed measurements, Atmospheric Chemistry and Physics, 21(24), 18669–18688. https://doi.org/10.5194/acp-2021-203 För mer information se den engelska katalogsidan: https://snd.gu.se/en/catalogue/study/2021-125 Accurate predictions of snowfall require good knowledge of the microphysical properties of the snow ice crystals and particles. Shape is an important parameter as it strongly influences the scattering properties of the ice particles, and thus their response to remote sensing techniques such as radar measurements. The fall speed of ice particles is another important parameter for both numerical forecast models as well as representation of ice clouds and snow in climate models, as it is responsible for the rate of removal of ice from these models. The particle mass is also a key quantity as it connects the cloud microphysical properties to radiative properties. The ground-based in-situ instrument Dual Ice Crystal Imager (D-ICI) has been used in Kiruna, Sweden, to determine snow ice particle properties and fall speed simultaneously. D-ICI takes two high-resolution images of the same falling ice particle from two different viewing directions, a top view and a side view. Both images have a pixel resolution of approximately 4 μm/pixel and an optical resolution of approximately 10 ...